Female voices in translation: an interrogation of a dynamic translation decade for contemporary Chinese women writers, 1980–1991. (2nd January 2019) - Jiang, Mengying
ABSTRACT: Contemporary Chinese women writers have long been underrepresented in English translation. However, they received considerable attention from Anglophone publishers during the 1980s. Such a dynamic translation scene was prompted by an upsurge of female writers in China after 1978, when political restrictions on literature were loosened, and an increased interest on the part of Western feminists in female experience from different ethnicities. This article adopts Pierre Bourdieu's field theory to analyse the selection and paratextual strategies adopted by two categories of translation agents: the dominant Anglophone publishers and the subversive feminist translators. It argues that Anglophone publishers were governed by a dominant political translation discourse that resulted from a dual patriarchal control: the Chinese nationalist agenda imposed on the writers' feminist preoccupations and the predilection of Western ideology for the politics of China. This seemingly thriving translation turn for Chinese women writers was in fact still subject to a voyeuristic gaze that positioned China as the subaltern other. It was women translators who maintained a subversive position against the orthodox translation discourse, thus contributing to what could be called a predominantly feminist translation era for contemporary Chinese women writers.